The Danyoung Classification Correlation with The Severity of Allergic Rhinitis and Symptoms Duration - Tri Wirattami, Ayunita; Agustina, Tanti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The Danyoung classification characterizes progressive endoscopic changes in the nasal mucosa of allergic rhinitis (AR) patients, but its clinical correlation with disease severity and chronicity remains unestablished. This cross-sectional study aimed to determine the association between Danyoung stages (1: hypertrophic, 2: dimple, 3: wrinkled) and AR symptomatology. Fifty AR patients from a tertiary allergy-immunology clinic were enrolled over a six-month period. Data on symptom duration, profile, and ARIA-based severity (intermittent/persistent, mild/moderate-severe) were collected. Nasoendoscopic examination was performed for Danyoung staging. Statistical analysis using chi-square tests demonstrated no significant association between Danyoung stage and symptom duration (p=0.85) or clinical disease severity (p=0.96). The findings indicate that the Danyoung classification, as an objective morphological descriptor, is not a statistically significant predictor of symptom-based AR severity or chronicity in this patient cohort. This suggests that the progression of endoscopic nasal mucosal changes may follow a pathway independent of the clinical parameters defined by ARIA guidelines, limiting its utility as a standalone clinical prognostic tool.